Congenital Cataracts; Its Laterality and Association with Consanguinity - Ali Raza, Waseem Akhter, Afia Matloob Rana (Pakistan Journal of Ophthalmology, 2014)
Purpose: To study the frequency of laterality (bilateral vs. unilateral) and its importance among congenital cataracts. We also investigated consanguinity as a risk factor in congenital cataract cases. Material and Methods: This study was conducted in Ophthalmology department, Holy family hospital, Rawalpindi, from 2nd January 2013 to 2nd February 2014. A total of 112 eyes and 86 patients in age range from 3 months to 26 years and all types of visually significant congenital cataracts total or partial without prior history of ocular trauma and syndromic association were recruited for the study. Frequency distribution, test of significance was carried out using Statistical Package for Social Sciences Version 20.0. Results: A total of 112 cases (61 males, 51 females) were recruited in the study. There was no statistically significant difference between different age groups and gender (p=0.2). The unilateral cases were 19.6% and bilateral were 80.4%. Consanguinity was present in 69.6% (n=78) and absent in 30.4% (n=34). The difference was statistically significant (p=0.00). Conclusion: Bilateral congenital cataract is a more common presentation as compared to unilateral cataract. Consanguinity is an important risk factor for congenital cataract especially bilateral cataracts. Key Words: Congenital Cataracts; ocular trauma, Syndromic association